Numerical Solution for Network Simulation Model of Free Convective Heat and Mass Transfer from a Vertical Cone - Bapuji Pullepu (Science Faculty of Chiang Mai University, 2019)
A two dimensional mathematical model is presented for the unsteady laminar free convective flow with heat and mass transfer over an incompressible viscous fluid past a vertical permeable cone with uniform wall temperature and non-uniform wall concentration combined with the effects of chemical reaction. The dimensionless governing boundary layer equations of the flow that are transient, coupled and nonlinear partial differential equations are solved using the network simulation model (NSM), a robust numerical technique which demonstrates high efficiency and accuracy and the computer code Pspice. The velocity, temperature and concentration profiles have been studied for various parameters, namely chemical reaction parameter l, Schmidt number Sc, Prandtl number Pr, buoyancy ratio parameter N and surface concentration power law exponent m are analyzed graphically. The present results are compared with the results available in the open literature and are found to be in excellent agreement.